1995
DOI: 10.1002/hep.1840210507
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of octreotide in patients with hepatic cirrhosis

Abstract: Octreotide is thought to reduce splanchnic and variceal blood flow with minimal effects on the systemic circulation in cirrhotic patients with portal hypertension. However, we noticed significant bradycardia in some patients immediately after administration of bolus doses of octreotide. Therefore, we investigated the effect of intravenous octreotide on systemic hemodynamics in 59 patients with cirrhosis. In two double-blind, placebo-controlled protocols, 32 patients received a 25-micrograms bolus and 20 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…Some studies have found a decrease in portal pressure (41), while others have failed to achieve such a bene cial effect (19)(20)(21). A transient reduction of the azygos blood ow and a rapid cardiovascular effect has also been reported (22,42). The heterogeneity of these results may be due to the time used to measure the effects following octreotide administration.…”
Section: Discussionmentioning
confidence: 85%
“…Some studies have found a decrease in portal pressure (41), while others have failed to achieve such a bene cial effect (19)(20)(21). A transient reduction of the azygos blood ow and a rapid cardiovascular effect has also been reported (22,42). The heterogeneity of these results may be due to the time used to measure the effects following octreotide administration.…”
Section: Discussionmentioning
confidence: 85%
“…However, Gines et al indicated that the use of SMS might impair renal function in cirrhotic patients, mainly those with ascites (17). In addition, octreotide produced a transient effect (18,19) or no effect (20)(21)(22) on systemic hemodynamics in nonazotemic cirrhotic patients, while the effects on renal hemodynamics and function were controversial (16,(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 98%
“…However, any meaningful observations from subset analyses are difficult to derive owing to the small sample size. Provided that the mechanisms of action of OCT on human splanchnic vasculature are incompletely known, 13 one could speculate on variable effects of the OCT on cell membrane receptors of vascular smooth muscle, 14 on the release of gastrointestinal hormones, such as glucagon that have been reported to affect splanchnic blood flow, 15 or on possible systemic effects after OCT injection, 16,17 although this seems unlikely in view of the stable arterial blood pressure.…”
Section: Discussionmentioning
confidence: 98%